Influence of alternative fuels on combustion and characteristics of particulate matter morphology in a compression ignition diesel engine. (April 2020) - Fayad, Mohammed A.; Tsolakis, Athanasios; Martos, Francisco J.
Abstract: The improvement of combustion and harmful emissions reduction has been driven by multiple factors; alternative fuels can be one of the important factors. In this study, Gas-to-Liquid (GTL) and Ethanol-RME-Diesel blend are used as an alternative fuels in a single cylinder diesel engine. The impact of alternative fuel on particulate matter (PM) characteristics and gaseous emissions were studied. These results reveal that ethanol blend increases the in-cylinder pressure and rate of heat release (ROHR) compared to the GTL and diesel fuel by 4% and 13% respectively. The particulate size distribution (PSD) was smaller from the combustion of ethanol blend compared to diesel and GTL fuel. The experimental results indicated that the ethanol blend produces smaller size of soot agglomerate and lower number of soot primary particles ( n po ) than to the rest of fuel. Furthermore, it can be observed that the soot particles emitted from ethanol blend has less spherical shape due to smaller fractal dimension ( D f ) than to the diesel and GTL fuel. It is found that the NOX emissions were lower from the combustion of GTL fuel than ethanol blend and diesel fuel. Highlights: PM agglomerates and primary particles emitted from alternative fuels combustion are smaller. PM agglomerate emitted from ethanol blend has lower fractal dimension and smaller size than GTL and diesel fuel particles. Ethanol blend enhance the combustion performance and decreases the soot formation. PM/soot oxidation from ethanol blend combustion is occur in short time and lower temperatures compared to GTL and ULSD.